Nonsurgical therapy for hydrocephalus: a comprehensive and critical review. Issue 1 (December 2015) - Del Bigio, Marc; Di Curzio, Domenico
Abstract Pharmacological interventions have been tested experimentally and clinically to prevent hydrocephalus and avoid the need for shunting beginning in the 1950s. Clinical trials of varied quality have not demonstrated lasting and convincing protective effects through manipulation of cerebrospinal fluid production, diuresis, blood clot fibrinolysis, or manipulation of fibrosis in the subarachnoid compartment, although there remains some promise in the latter areas. Acetazolamide bolus seems to be useful for predicting shunt response in adults with hydrocephalus. Neuroprotection in the situation of established hydrocephalus has been tested experimentally beginning more recently. Therapies designed to modify blood flow or pulsation, reduce inflammation, reduce oxidative damage, or protect neurons are so far of limited success; more experimental work is needed in these areas. As has been recommended for preclinical studies in stroke and brain trauma, stringent conditions should be met for preclinical studies in hydrocephalus.